Information security : principles and practice - Stamp, Mark. (Hoboken, NJ : Wiley, 2011)
"Featuring a wide array of new information on the most current security topics, this book provides everything readers need to tackle any information security challenge. Focusing on cryptography, access control, protocols and software, this Second Edition features a greatly expanded set of homework problems; an appendix that covers necessary background information, like networking basics; a solutions manual and a comprehensive set of classroom-tested PowerPoint slides; and many new figures, tables, and graphs to clarify complex topics and problems. Students and instructors in information technology, computer science, and engineering, as well as professionals in these fields will depend on this text"--
Includes bibliographical references (p. 531-571) and index.
Keywords: Computer security; COMPUTERS / Security / General